Examining Sexual Function Among Individuals With HIV in a Midwestern US Urban Outpatient Clinic Setting - E. Shacham Phd, Med; Julia D. López PhD, MPH, LCSW; P. Souza LCSW, MPH; E. Turner Overton MD (Journal of the International Association of Providers of AIDS Care, 2017)
The role of sexual function and its impact on HIV management have been inadequately evaluated. A cross-sectional study in 2009 of 202 patients with HIV were recruited to examine sexual function and psychosocial/HIV management factors. Analyses assessed the relationship between sexual function, sociodemographic factors, biomedical markers, and depressive symptomology. The M-Estimator compared differences in the means of the HIV, cancer survivors, and the normative cohorts. More than 75% were on combination antiretroviral therapy, of which 70% had suppressed HIV viral loads. Patients with unsuppressed HIV viral loads reported lower rates of arousal. Better overall health was associated with higher rates of overall sexual function, arousal, and interest. Compared to the normative and cancer survivor cohorts, mean sexual function was significantly lower in the HIV-infected cohort in all subscales, except for masturbation. These findings suggest lower sexual function impacts individuals with HIV in ways related to negative biomedical and psychosocial factors.